Penerapan Model Pembelajaran The Power Of Two untuk Meningkatkan Hasil Belajar IPS Pada Siswa Kelas IV SDN 104/I Simpang Jebak - Firman Khaidir; Panut Setiono; Muspida Heri (Jurnal Gentala Pendidikan Dasar, 2019)
This study aims to determine how the application of learning models The Power Of Two to improve social studies learning outcomes in grade IV SDN 104/I Simpang Jebak. This study is a class action (Classroom Action Reasearch). Concluded this research : Using the model of learning The Power of Two can enhance the activity of student learning and learning outcomes in social studies lesson on the material development of production teknlogi, trasnportasi, and communication in class IV SDN 104/I Simpang Jebak. Student activity through the application of learning models The Power of Two reached an average of 53.5% (less criteria) in cycle 1, then the teacher can make improvements increased the activity to 63.5% (enough criteria) in cycle 2 and cycle 3 more increased to 75.4% (Criterion good) student learning results from tests (Evaluation) cycle I reached an average of 57% (or less), then the teacher make improvements in cycle 2 study results increased by an average of 64% (enough) and the third cycle is increased to 75% (good). Learning model The Power Of Two can improve student learning outcomes in social studies learning the material development of production technology, transportation and comunication class IV SDN 104/I Simpang Jebak.